Aplikasi Mobile untuk Manajemen Peminjaman Ruang Kelas Studi Kasus Sekolah Bhineka Tunggal Ika - Nicholas Janitra; Nizirwan Anwar (Prosiding SISFOTEK, 2024)
This research aims to design and implement a mobile application for borrowing rooms and classes at a school called "Sekolah Bhinneka Tunggal Ika". The research methods used include observation and interviews. The research results show that a mobile application-based room lending information system can make borrowing faster and more efficient. This application makes it easier for users to access lending services and helps administrative staff manage loan data in a database and properly record it. In conclusion, implementing the mobile application for borrowing rooms at the Bhinneka Tunggal Ika School succeeded in optimizing the borrowing process, making it faster, more efficient and easier to access for users and helping the school administration manage data.